Outside income and moral hazard: the elusive quest for good politicians - Stefano Gagliarducci; Tommaso Nannicini; Paolo Naticchioni (Institute for the Study of Labor (IZA), 2008)
In most modern democracies elected officials can work in the private sector while appointed in parliament. We show that when the political and market sectors are not mutually exclusive, a trade-off arises between the quality of elected officials and the effort they exert in political life. If high-ability citizens can keep earning money outside of parliament, they will be more likely to run for election; for the same reason, they will also be more likely to shirk once elected. These predictions are confronted with a unique dataset about members of the Italian Parliament from 1996 to 2006. The empirical evidence shows that bad but dedicated politicians come along with good but not fully committed politicians. There is in fact a non-negligible fraction of citizens with remarkably high pre-election income who are appointed in parliament. These citizens are those who gain relatively more from being elected in terms of outside income. Conversely, they are less committed to the parliamentary activity in many respects, like voting attendance and bills sponsorship.
Keywords: D72; 320; Politicians; moral hazard; adverse selection; absenteeism; outside income; Public Choice; Politiker; Moral Hazard; Italien